EDUKASI PENANGANAN DAN PENGELOLAAN SAMPAH SKALA RUMAH TANGGA DI KELURAHAN RIJALI, KOTA AMBON - Safinah Yulianty Sitania; Pradina Sukirno; Mohamad S Tuharea; Morgan Ohiwal (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Garbage is all waste generated by human and animal activities. waste is divided into solid waste, mud, liquid, and gas which is disposed of because it is no longer needed. Among all sources of waste, household waste is the largest waste, reaching 40.7%. As a village located in the center of Ambon city and along the river, Rijali Village has many problems with waste management, where all household and industrial waste are dumped into rivers which affects on water quality and public health. This problem becomes more serious when the increase in the amount of waste is not accompanied by the government's ability to provide adequate waste management facilities and participation from the community. Therefore, active participation from the community is needed to create a more comprehensive waste management system starting from the household scope based on the 5R principle (Reduce, Reuse, Recycle, Replant, Replace). The objectives of this service activity are: (1) to educate the community, especially the Rijali Village community about efficient waste management starting from the household, (2) to increase public awareness regarding conservative and environmentally friendly lifestyles (3) to introduce the waste bank system to the community. The target of this community service activity is to increase the level of knowledge and awareness of the community in implementing a clean and healthy lifestyle in everyday life.